Unraveling architectural RNAs: Structural and functional blueprints of membraneless organelles and strategies for genome-scale identification - Fujiwara, Naoko; Ueno, Tsuyoshi; Yamazaki, Tomohiro; Hirose, Tetsuro (Biochimica et biophysica acta. General subjects, 2025)
Architectural RNAs (arcRNAs) are long noncoding RNAs that serve as structural scaffolds for membraneless organelles (MLOs), facilitating cellular organization and dynamic responses to stimuli. Acting as blueprints for MLO assembly, arcRNAs recruit specific proteins and nucleic acids to establish and maintain the internal structure of MLOs while coordinating their spatial relationships with other organelles. This organized framework enables precise spatiotemporal regulation, allowing for targeted control of transcription, RNA processing, and cellular responses to stress. Notably, arcRNAs exhibit the “semi-extractable” feature, a property derived from their stable binding to cellular structures, making them partially resistant to conventional RNA extraction methods. This unique feature serves as a useful criterion for identifying novel arcRNAs, providing an opportunity to accelerate research in long noncoding RNAs and deepen our understanding of their functional roles in cellular processes. •A subset of lncRNAs that function as scaffolds for membraneless organelles is defined as ‘architectural RNA (arcRNA).•Despite their important role as regulators of cellular processes, the number of definitively identified arcRNAs remains limited.•NEAT1_2 arcRNA scaffolds paraspeckles, acting as a blueprint for their organization and interaction with other organelles.•HSATIII arcRNAs scaffold nuclear stress bodies and regulate mRNA splicing, acting as reaction crucible and molecular sponge.•RNA semi-extractability, derived from stable binding with cell components, serves as a clue for identifying novel arcRNAs.